Motivasi Kerja dalam Meningkatkan Kinerja Oganisasional (Sebuah Kajian Konseptual dalam Perspektif Islam) - Ganika, Gerry (Sains: Jurnal Manajemen dan Bisnis, 2024)
The article explores the potential relationship between motivation and spiritual values in Islam in an organizational setting. Spirituality is a factor in shaping the personality and behavior, so it is not an exaggeration that spirituality as a subject in the study of business management and organizational behavior. Study of motivation based on Islamic spiritual perspective is necessary to find a balance and development of existing theories of motivation. The level of motivation in the perspective of Islam, which started in the Middle Ages are a completely different understanding of thoughts that have been used in the context of human psychology and organizational management. Motivation in spirituality of Islam composed of four levels conditions: (1) Sawala; drive by a physiological and material motivational impulse, (2) Amara; drive by physiological, psychological and material motivational impulse, (3) Lawama; drive by physiological, material, psychological and intellectual and involve a bit of spirituallty, (4) Mutamainna; drive by the stimulation of all needs based on the value of spirituality as the primary basis. At the stage of Mutamainna, it reflects a harmony between all needs, and has major implications for the organizational and business management practices and behavioral to achieve the organizational performance.